Determination of the Leaf Surface Of Cotton Variety Termiz-202 With Ingichka Fiber - Qodirov Ahmadjon Abduraufovich; Aymatov Safarniyoz Shaymardon o‘g‘li; Xayrullaev talaba Jonibek Fatullaning o‘g‘li (Scientific Trends, 2022)
In the conditions of swampy soils of Surkhondarya region, the data on the development periods of the leaf surface of fine-fiber Termiz -202 cotton, including combing, flowering-harvesting, ripening and before defoliation , are presented .
Keywords: Campsis Radicans (Seem), China Wisteria - Wisteria Sinensis ( Sums ), Japanese Beauty – Lonicera Japonica (Thumb)